2018
DOI: 10.1039/c7fo01619k
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a Ganoderma atrum polysaccharide against acrylamide induced oxidative damage via a mitochondria mediated intrinsic apoptotic pathway in IEC-6 cells

Abstract: The preventive role of a purified Ganoderma atrum polysaccharide PSG-1-F as a new dietary antioxidant against the intestinal toxicity of acrylamide (ACR) was investigated in vitro. Our results showed that ACR could induce oxidative stress in IEC-6 cells by the overproduction of reactive oxygen species (ROS) and malondialdehyde (MDA), and as well as the reduction in the activities of superoxide dismutase (SOD) and glutathione peroxidase (GSH-Px). In addition, the induction of a mitochondria-mediated intrinsic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Numerous studies have implied that mitochondrial apoptosis is involved in neuronal death in ACRinduced neurotoxicity. [34][35][36] In this present study, we proved that NR1 could resist ACR-induced neurotoxicity by regulating the mitochondrial apoptosis pathway. It is also the first time that NR1 has been proved to inhibit ACR-induced neurotoxicity.…”
Section: Discussionsupporting
confidence: 57%
“…Numerous studies have implied that mitochondrial apoptosis is involved in neuronal death in ACRinduced neurotoxicity. [34][35][36] In this present study, we proved that NR1 could resist ACR-induced neurotoxicity by regulating the mitochondrial apoptosis pathway. It is also the first time that NR1 has been proved to inhibit ACR-induced neurotoxicity.…”
Section: Discussionsupporting
confidence: 57%
“…Due to definite exposure of humans to acrylamide for various sources, probably detoxification of this compound inside the body can be a suitable approach to reduce its toxicity. It is well confirmed that oxidative stress and mitochondrial dysfunction have a main role in acrylamideinduced toxicity [11]. Therefore, natural compounds with antioxidant and antitumorigenic properties can probably play a promising role in inhibiting the toxicity caused by acrylamide.…”
Section: Introductionmentioning
confidence: 97%
“…The AA group and two low dose groups showed glomerular atrophy, and enlarged bowman's space (black arrow). There was no obvious pathological damage in the two high dose groups (SOD, CAT) and GSH, and increase the level of LPO in rats [36,37]. Our results showed that no obvious ataxia and hind limb valgus were observed in rats fed high doses of L. plantarum ATCC8014.…”
Section: Discussionmentioning
confidence: 51%